Methods for design and fabrication of nanosensors: the case of ZnO-based nanosensor - Gorup, Luiz Fernando; Amorin, Luís Henrique; Camargo, Emerson Rodrigues; Sequinel, Thiago; Cincotto, Fernando Henrique; Biasotto, Glenda [UNESP]; Ramesar, Naomi; La Porta, Felipe de Almeida (Elsevier, 2020)
Advanced materials research currently focuses on the design and fabrication of nanosensors and shows tremendous potential for the development of numerous applications in various areas of nanotechnology. The significant scientific and technological advances in materials design for nanosensor applications have wide-ranging economic implications. From a practical point of view, nanosensors are classified as either chemical or physical and usually comprise at least one nanoscale component. New technologies based on advanced nanoscale materials have considerable advantages over more traditional sensors. Nanosensors are typically very sensitive and can detect variations in concentrations of many types of target particles, including single viruses, proteins, and molecules in diverse and complex environments. Nanosensor fabrication is highly challenging, but there have been significant advances in research and development, particularly in terms of customizing fabrication methods for specific applications. There are many kinds of nanosensors and correspondingly many ways to manufacture them. Yet, the ability to create new nanoscale complex materials and devices in different desired configurations depends mainly on developing new approaches to materials synthesis. Here our emphasis that is motivated on highlighting the defect engineering may provide essential clues to improve our synthesis methods and understanding of their outstanding properties at the nanoscale. This chapter summarizes some examples of the design and fabrication of nanosensors based on ZnO nanocrystals, potentially serving a diverse range of applications, as described in detail. It also discusses the fundamental concepts behind the design and fabrication of these nanosensors in view of their many applications.
Keywords: electrochemical sensors; Electrodeposition; hydrothermal; nanosensors; thin film